2004
DOI: 10.1023/b:phot.0000046169.05296.9b
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub> Assimilation and Water Relations of Almond Tree (Prunus amygdalus Batsch) Cultivars Grown Under Field Conditions

Abstract: Gas exchanges and leaf water potential (ψ w ) of six-years-old trees of fourteen Prunus amygdalus cultivars, grafted on GF-677, were studied in May, when fruits were in active growing period, and in October, after harvesting. The trees were grown in the field under rain fed conditions. Predawn ψ w showed lower water availability in October compared with May. The lowest ψ w values at midday in May increased gradually afterwards, while in October they decreased progressively until night, suggesting a higher diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…---Non-stomatal effects may prevent photosynthetic activities as has been reported for eucalyptus (Rawat and Banerjee 1998), pistachio (Ranjbar et al 1999(Ranjbar et al , 2002, and almond (Matos et al 2004, Rouhi et al 2006. Salt stress can also lead to destruction of fine chloroplast structure and instability of pigment-protein complexes (Zaman et al 2002).…”
Section: Introductionmentioning
confidence: 92%
“…---Non-stomatal effects may prevent photosynthetic activities as has been reported for eucalyptus (Rawat and Banerjee 1998), pistachio (Ranjbar et al 1999(Ranjbar et al , 2002, and almond (Matos et al 2004, Rouhi et al 2006. Salt stress can also lead to destruction of fine chloroplast structure and instability of pigment-protein complexes (Zaman et al 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Thus, plants respond to salinity at nonstomatal and/or stomatal levels. Nonstomatal responses include instability of pigment-protein complexes and destruction of chloroplast structure (Zaman et al 2002), which inhibits photosynthetic activities (Matos et al 2004, Rouhi et al 2006. At the stomatal level, the stomatal activity is reduced and it limits photosynthesis (Lawlor and Cornic 2002) and photon flux energy used for photochemistry (Cornic 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, photosynthesis of fruit trees has been studied in banana (Thomas and Turner 2001), mango (Shivashankara and Mathai 2000), grape (Patakas et al 2003, Cohen et al 2005, apple (Jia andLi 2002, Mierowska et al 2002), almond (De Herralde et al 2003, Matos et al 2004, jujube (Su and Liu 2005), etc. But no research has been reported on apricot acclimation in controlled environments.…”
Section: Introductionmentioning
confidence: 99%